A Novel Multiparameter Scoring Model for Noninvasive Early Prediction of Ischemic Colitis: A Multicenter, Retrospective, and Real-World Study. Issue 6 (9th June 2021) - Li, Shan; Luo, Yiwei; Wang, Wei; Lu, Jinlai; Hu, Miao; Sun, Qinjuan; Yang, Xiaoqing; Han, Junyi; Zhong, Lan
Abstract : INTRODUCTION: Ischemic colitis (IC) is a common gastrointestinal ischemic disease caused by hypoperfusion or reperfusion injury. However, there are few studies on risk factors associated with poor prognoses of the disease. This study aimed to determine the predictors of poor prognoses in patients with IC and establish a prognostic scoring method with good internal and external validity for identifying severe cases in an early stage. METHODS: We established a prognosis model by conducting a multicenter, retrospective study of patients hospitalized with IC between November 2008 and May 2020. Predictive power was tested using 5-fold internal cross-validation and external validation. RESULTS: The following 6 factors were included in the prognostic model: neutrophil count, D-dimer level, ischemia of the distal ileum, ischemia of the hepatic flexure, ulceration, and luminal stenosis. The area under the receiver-operating characteristic curve for internal cross-validation of the prediction model was 86%, and that for external validation was 95%. During internal validation, our model correctly identified 88.08% of the patients. It was further found that patients younger than 65 years with a higher neutrophil-to-lymphocyte ratio and higher heart rate had poor prognoses. Patients aged 65 years and older with ischemia of terminal ileum, hepatic flexure, splenic flexure, and intestinal stenosis had poor prognoses. DISCUSSION: Patients with ischemia in the hepatic flexure and the distal ileum, endoscopic evidence of ulcer or stenosis, higher neutrophil counts, and higher D-dimer levels have worse prognoses. This information could aid in the selection of timely and appropriate treatment.